2008
DOI: 10.1086/525841
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of Protoplanetesimal Dust Agglomerates. II. Low‐Velocity Collision Properties

Abstract: For the investigation of collisions among protoplanetesimal dust aggregates, we performed microgravity experiments in which the impacts of high-porosity millimeter-sized dust aggregates into 2.5 cm high-porosity dust aggregates can be studied. The dust aggregates consisted either of monodisperse spherical, quasi-monodisperse irregular, or polydisperse irregular micrometer-sized dust grains and were produced by random ballistic deposition with porosities between 85% and 93%. Impact velocities ranged from $0.1 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 28 publications
5
63
2
Order By: Relevance
“…This is much less than the collision velocity achieved in protoplanetary disks. Our estimation on u col,crit for silicate aggregates is consistent with several laboratory experiments and numerical simulations for silicate aggregates (e.g., Blum & Wurm 2000Langkowski et al 2008;Güttler et al 2010;Paszun & Dominik 2009;Seizinger & Kley 2013), suggesting the difficulty of silicate dust growth.…”
Section: Introductionsupporting
confidence: 89%
“…This is much less than the collision velocity achieved in protoplanetary disks. Our estimation on u col,crit for silicate aggregates is consistent with several laboratory experiments and numerical simulations for silicate aggregates (e.g., Blum & Wurm 2000Langkowski et al 2008;Güttler et al 2010;Paszun & Dominik 2009;Seizinger & Kley 2013), suggesting the difficulty of silicate dust growth.…”
Section: Introductionsupporting
confidence: 89%
“…This is a crucial assumption in which collisional outcomes like bouncing are a priori not possible because these do not take place at the low-N part of the simulations. Bouncing of aggregates is observed in laboratory experiments (Blum & Münch 1993;Blum 2006;Langkowski et al 2008;Weidling et al 2009), whereas it does not occur in our simulations. For silicates, bouncing occurs at sizes above approximately 100 μm (i.e., N > 10 9 particles) and is not fully understood from a microphysical perspective.…”
Section: B4 Limitations Of the Collision Recipecontrasting
confidence: 68%
“…Wada et al (2011) obtained similar results when performing molecular dynamics simulations of collisions of CPE aggregates featuring a hard sphere. Langkowski et al (2008) found that molding an aggregate significantly alters the outcome of a collision experiment. However, Kothe et al (2013) analyzed aggregates used in their collision experiments with X-ray computer tomography imaging and could not find any compacted outer layers.…”
Section: Discussionmentioning
confidence: 99%